Padumalāla Punnālāla Bakhśī para kendrita - Agravāla, Mahāvīra; Miśrā, Abhaya Kumāra (Śrī Prakāśana, 2002)
Contributed articles on the life and works of Padumalāla Punnālāla Bakhśī, 1894-1971, Hindi author.